Implementasi Diagram UML (Unified Modelling Language) Pada Perancangan Sistem Informasi Penggajian - Setiaji Setiaji; Ricki Sastra (Universitas Bina Sarana Informatika, 2021)
Companies need an information system that supports and can provide fast and accurate data. This research was conducted as an effort to improve the existing payroll system so that it is more effective and efficient. At this time several companies engaged in the payroll system services are still at their maximum, starting from recording attendance to payroll, making it possible when the process takes place there are errors in payroll, inaccurate reports made and late in searching for the required data. The research information system uses object-oriented Unified Modeling Language (UML) software modeling. Researchers use Unified Modeling Language modeling with the aim that the desired system can be provided properly so that problems in the existing system are resolved. This uml modeling process begins with analyzing the system's needs and implementing it in usecase traffic diagrams by making class diagrams, sequence diagrams, and activity diagrams. UML software modeling also provides benefits in software development and is able to monitor the flow or system flow expected by the company. This research also uses the approach waterfall method, namely analysis, design, code generation program, testing and maintenance in designing. This information system design is the best solution to solve problems that exist in the payroll system. The payroll system that utilizes software to support the process provides a very effective contribution to the company and the development process will still be carried out for existing problems.